HOW IS THE DYNAMIC THINKING PROCESS OF PROFICIENT’ STUDENTS IN SOLVING TRANSFORMATION GEOMETRY PROBLEMS? - Pamungkas, Megita Dwi; Waluya, Stevanus Budi; Mariani, Scolastika; Isnarto, Isnarto (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Dynamic thinking is a crucial cognitive skill that enables students to solve complex problems in geometry effectively. This study investigates the characteristics of dynamic thinking among prospective mathematics teachers, focusing on the four key aspects: technique, conceptualization, monitoring, and perception. While previous research has identified these aspects, the specific problem-solving characteristics of dynamic thinking in mathematical contexts remain unexplored. This qualitative study was conducted at Tidar University, involving 54 prospective mathematics teachers identified as dynamic thinkers. Data were collected through a two-stage problem-solving test, structured observations, and in-depth interviews. The research instruments underwent a validation process to ensure reliability. Data analysis followed a systematic approach involving reduction, presentation, and verification to extract patterns of dynamic thinking among proficient problem solvers. The results indicate that students who exhibit proficient dynamic thinking demonstrate completeness and consistency in all four aspects. They effectively integrate multiple strategies, adapt their approaches in response to challenges, and maintain a reflective understanding of their problem-solving processes. Additionally, proficient dynamic thinkers show a higher degree of flexibility and spatial reasoning in geometry problems. This study contributes to the existing body of knowledge by identifying and describing the specific characteristics of dynamic thinking in mathematical problem-solving. The findings provide valuable insights for teacher education programs, emphasizing the need to cultivate dynamic thinking skills among prospective math educators. Future research can explore dynamic thinking across different mathematical domains and cognitive frameworks.